Development and Validation of an Instrument to Measure Critical Thinking in Respiratory Care - Lynda Thomas GoodFellow; Lynda Valentine; Margaret E. Holt (Adult Education Research Conference, 1999)
Purpose - to establish the reliability and validity of an instrument to measure critical thinking among respiratory therapists. Questions derived from Mishoe's (1995) study, expert therapists and the literature. Content validity established. Pilot instrument tested with reliability = 0.94 (Cronbach's alpha). Instrument can be used to measure critical thinking in respiratory care.